2016
DOI: 10.3892/ijo.2016.3459
|View full text |Cite
|
Sign up to set email alerts
|

EIF3D silencing suppresses renal cell carcinoma tumorigenesis via inducing G2/M arrest through downregulation of Cyclin B1/CDK1 signaling

Abstract: There are no effective therapies for advanced renal cell carcinoma (RCC), except for VEGFR inhibitors with only ~50% response rate. To identify novel targets and biomarkers for RCC is of great importance in treating RCC. In this study, we observed that eukaryotic initiation factor 3d (EIF3D) expression was significantly increased in RCC compared with paracarcinoma tissue using immunohistochemistry staining and western blot analysis. Furthermore, bioinformatics meta-analysis using ONCOMINE microarray datasets s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 24 publications
3
32
0
2
Order By: Relevance
“…According to the histomorphology, immunophenotype and genetic characteristics, RCC is classified into three major histological subtypes: clear cell RCC (ccRCC), comprising about 75-80%; papillary RCC (pRCC), comprising about 10-15%; and chromophobe RCC (cRCC), comprising about 4-5% [ 2 , 3 ]. Currently, surgical remains the mainstay of treatment for localized or early-stage RCC [3] . Unfortunately, some patients with localized early-stage RCC will develop metastatic or advanced RCC after radical nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the histomorphology, immunophenotype and genetic characteristics, RCC is classified into three major histological subtypes: clear cell RCC (ccRCC), comprising about 75-80%; papillary RCC (pRCC), comprising about 10-15%; and chromophobe RCC (cRCC), comprising about 4-5% [ 2 , 3 ]. Currently, surgical remains the mainstay of treatment for localized or early-stage RCC [3] . Unfortunately, some patients with localized early-stage RCC will develop metastatic or advanced RCC after radical nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Eukaryotic translation initiation factor 3 (EIF3) is one of the largest and most complex eukaryotic translation initiation factors containing 13 subunits (eIF3a-eIF3m), which plays an important role in the regulation of eukaryotic translation [10] . EIF3 promotes mRNA binding to 40S subunits and prevents premature binding of large ribosomal subunits to regulate eukaryotic protein synthesis [3] . Emerging studies have demonstrated that eIF3 plays a role in tumorgenesis and tumor progression [11] .…”
Section: Introductionmentioning
confidence: 99%
“…MOAP1 participates in the internal and external pathways of cell death and activates the apoptotic protein BAX of Bcl-2 family [25]. Studies have shown that knockout of EIF3D significantly induces G2/M arrest and apoptosis by down-regulating cyclin B1 and upregulating p21 [26].…”
Section: Discussionmentioning
confidence: 99%
“…(a) 15 genes such as apoptotic regulator 1 (MOAP1) and eukaryotic translation initiation factor 3 subunit D (EIF3D) that were reported to regulate cell cycle, apoptosis, and cell death [25,26]. USP17L6P had a positive regulation relationship with TP53-regulated inhibitor of apoptosis (TRIAP1) that was associated with apoptosis and cell death [27].…”
Section: Coexpression Networkmentioning
confidence: 99%
“…Besides, the relation between gene expression and various clinical data with respect to pathology, prognosis, metastasis and drug resistance can also be analyzed using the ONCOMINE microarray dataset. Increased numbers of studies have begun utilizing the datasets to validate and explore their research results (1719). Using the ONCOMINE microarray dataset, the present study found that PPP5C was upregulated in BCa, which was correlated with T stage, malignant grade and survival of BCa patients (Fig.…”
Section: Discussionmentioning
confidence: 99%